Wood Frog and Boreal Chorus Frog Distribution and Habitat Associations in Wapusk National Park, Cape Churchill, Manitoba: 2005 Summary Report - Andersen, David E; Boal, Clint W; Reiter, Matthew E (2005)
Concern about amphibian populations at a global scale has resulted in recent efforts to establish monitoring programs for amphibians in North America (e.g., North American Amphibian Monitoring Program; Weir and Mossman 2004) and elsewhere, although these monitoring efforts have not been extended to subarctic regions. Distribution, abundance, population dynamics, and habitat relationships of anurans that inhabit subarctic regions are poorly understood, and anuran monitoring protocols developed for temperate regions may not be useful across large roadless areas of northern landscapes. Arctic and sub-arctic regions of North America are also areas predicted to experience changes in climate, and in some areas, have experienced habitat alteration due to high rates of herbivory by breeding and migrating waterfowl, especially snow geese (Chen caerulescens). Environmental and habitat changes may influence the distribution and abundance of anurans that inhabit arctic and subarctic regions (Wassersug 1992, Crump et al. 1999)